KUALITAS PELAYANAN PUBLIK DI KANTOR KELURAHAN PULAU KODINGARENG KOTA MAKASSAR - Wanda, Wanda; Tahir, Muhammad; Syarif, Ahmad (Universitas Muhammadiyah Makassar, 2024)
This study aims to determine the quality of public services at the Kodingareng Island Village Office, Sangkarrang District, Makassar City. The type of research used is qualitative research. The results showed that the quality of public services implemented in the Kodingareng Island Village Office, Sangkarrang District, Makassar City was seen from the dimensions of physical evidence (tangibles), such as office facilities which were still inadequate. 2) dimension (reliability) or employee reliability in providing services to the community has been achieved. 3) dimensions (responsiveness) or responsiveness of employees in providing services have been implemented. 4) dimensions (assurance) or service guarantees have not been maximally applied in the time frame. Also, 5) dimension (emphaty) or empathy in this case the concern of employees in providing services to the community has been achieved and implemented.